Dampak Hubungan Pertemanan Tidak Sehat Terhadap Kesehatan Mental Dan Prestasi Belajar Pada Remaja - Puput Tri Ayu Anggraini; Ellen Prima (CV. SINAR HOWUHOWU, 2026)
Adolescence is a crucial developmental period marked by an increased need for social relationships, particularly friendships. However, not all friendships positively influence adolescent development. One form of relationship that can have a significant negative impact is toxic friendship, which is generally characterized by harmful and manipulative behavior and a lack of genuine emotional support. This phenomenon is increasingly common among adolescents today and has the potential to significantly impact various important aspects of their lives. This article aims to examine in-depth the impact of toxic friendships on adolescents' mental health and academic achievement. The method used in this research is a literature review, which examined various relevant journals and scientific articles. Comprehensive data was obtained from credible academic sources that discuss the relationship between friendship quality, psychological well-being, and academic achievement in adolescents. The results indicate that toxic friendships can cause chronic stress, anxiety, feelings of worthlessness, and low self-esteem, significantly reducing adolescents' psychological well-being. Furthermore, these unhealthy friendships have also been shown to disrupt concentration in learning, decrease academic motivation, and ultimately lead to decreased academic achievement. Therefore, concrete preventative measures are needed through education about the importance of healthy friendships, improving interpersonal communication skills, and providing strong emotional support from family and school. With a positive and supportive social environment, adolescents can develop optimally, both mentally and academically.